2021
DOI: 10.1177/0975425321997785
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Spatial Metrics and Population Data in Mapping the Rural-Urban Transition and Exploring Models of Urban Growth in Hanoi, Vietnam

Abstract: The process by which cities (or urban areas) expand over time has remained a key focus for geographers, ecologists and other scientists interested in urban phenomena for decades. This study investigated the use of spatial metrics and population data for defining and mapping rural-urban transition zones in Hanoi and exploring urban growth models. The analysis showed that in 2010, about 30% of communes within Hanoi could be defined as rural, 38% as peri-urban and 32% as urban. The peri-urban communes showed a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…It is estimated, for example, that approximately 60% do not have pipeline water and about 50% do not have a system to dispose of solid garbage in urban and rural regions of Hoi An (Pham Phu et al, 2021). Poor and insufficient transport networks have also made urban/rural linkages weak (Baffoe et al, 2021; Nong et al, 2021; Tue et al, 2015). Services such as health, education, communications and business could be restricted from their important roles by deficient information and communication technology infrastructures inside periurban and rural communities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated, for example, that approximately 60% do not have pipeline water and about 50% do not have a system to dispose of solid garbage in urban and rural regions of Hoi An (Pham Phu et al, 2021). Poor and insufficient transport networks have also made urban/rural linkages weak (Baffoe et al, 2021; Nong et al, 2021; Tue et al, 2015). Services such as health, education, communications and business could be restricted from their important roles by deficient information and communication technology infrastructures inside periurban and rural communities.…”
Section: Resultsmentioning
confidence: 99%
“…It was recommended by the people themselves that the proposed relational infrastructure in the policies of Hoi An city be green, sustainable and inexpensive. The government must be motivated in its efforts to upgrade core infrastructures, integrated transport systems (e.g., expressways and roads), water-energy supplies, household irrigation facilities and value-added processing facilities (Baffoe et al, 2021; Nong et al, 2021; Tue et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…An understanding of population dynamics is critical for sustainability and resilience for several reasons. A great number of authors have suggested that the fine scale mapping of population and population patterns and dynamics over time provides an accurate indication of urbanisation-associated human-environmental processes [100][101][102]. The share land under construction in 2010 decreased by 42.4% between 2010 and 2020.…”
Section: Spatiotemporal Patterns Of Urbanisation 2010-2020mentioning
confidence: 99%
“…Peri-urban zones are transitional zones between urban and rural districts with infrastructure systems such as water, sanitation, power, and transport in many of these areas remaining poor, and typically following rather than preceding development. This typically results in both overloaded engineered and institutional infrastructure and a loss of natural and social infrastructure [19,102,[126][127][128][129][130]. Previous studies have warned that such heterogeneous and fragmented landscapes can lead to inadequate development processes, unequal allocation of services and investment, ignorance of environmental protection, and cultural preservation [131][132][133][134].…”
Section: Peri-urbanisation Plot-by-plotmentioning
confidence: 99%
“…The auxiliary data from various sources can be combined for gridded population mapping via machine learning regression. It was demonstrated that location-based services (LBS) data, derived from mobile phones, Baidu map, Tencent LBS, Sina Weibo, and so on, offer the possibility of illustrating gridded population maps more accurately and finely in urban areas [11,22,[64][65][66][67][68][69][70][71]. In particular, the accuracy of gridded population maps can be improved significantly through the integration of remote sensing data and LBS data [72].…”
Section: Principal Findings and Meaningful Implicationmentioning
confidence: 99%